The DYD-RCT protocol: an on-line randomised controlled trial of an interactive computer-based intervention compared with a standard information website to reduce alcohol consumption among hazardous drinkers - Godfrey Christine; Thompson Simon G; White Ian R; Khadjesari Zarnie; McCambridge Jim; Murray Elizabeth; Linke Stuart; Wallace Paul (BMC, 2007)
Abstract Background Excessive alcohol consumption is a significant public health problem throughout the world. Although there are a range of effective interventions to help heavy drinkers reduce their alcohol consumption, these have little proven population-level impact. Researchers internationally are looking at the potential of Internet interventions in this area. Methods/Design In a two-arm randomised controlled trial, an on-line psychologically enhanced interactive computer-based intervention is compared with a flat, text-based information web-site. Recruitment, consent, randomisation and data collection are all on-line. The primary outcome is total past-week alcohol consumption; secondary outcomes include hazardous or harmful drinking, dependence, harm caused by alcohol, and mental health. A health economic analysis is included. Discussion This trial will provide information on the effectiveness and cost-effectiveness of an on-line intervention to help heavy drinkers drink less. Trial registration International Standard Randomised Controlled Trial Number Register ISRCTN31070347